Comparison of nitrification rates in blueberry and forest soils - Paul, Eldor A., author; Ravenscroft, John, author; Serce, Sedat, author; Throop, Philip A., author; Hanson, Eric J., author; American Society for Horticultural Science, publisher (Colorado State University. Libraries, 2002)
Highbush blueberries (Vaccinium corymbosum L.) are long lived perennial plants that are grown on acidic soils. The goal of this study was to determine how blueberry cultivation might influence the nitrification capacity of acidic soils by comparing the nitrification potential of blueberry soils to adjacent noncultivated forest soils. The net nitrification potential of blueberry and forest soils was compared by treating soils with 15N enriched (NH4)2SO4, and monitoring nitrate (NO3--N) production during a 34-day incubation period in plastic bags at 18°C. Net nitrification was also compared by an aerobic slurry method. Autotrophic nitrifiers were quantified by the most probable number method. Nitrate production from labeled ammonium (15NH4+) indicated that nitrification was more rapid in blueberry soils than in forest soils from six of the seven study sites. Slurry nitrification assays provided similar results. Blueberry soils also contained higher numbers of nitrifying bacteria compared to forest soils. Nitrification in forest soils did not appear to be limited by availability of NH4+ substrate. Results suggest that blueberry production practices lead to greater numbers of autotrophic nitrifying bacteria and increased nitrification capacity, possibly resulting from annual application of ammonium containing fertilizers.
Publisher version: http://journal.ashspublications.org/content/127/1/136.abstract.
Keywords: fertilization; nitrogen; Vaccinium corymbosum; nitrate; ammonium; isotopes; mineralization